Microplastic Contamination: An Emerging Concern for the Aquatic Environment (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
Microplastics (MPs) are so widely dispersed and abundant throughout the globe that many scientists consider them to be important markers of the recent and current time - Plasticene. The pollution of aquatic ecosystems by plastic litter is considered a common topic of serious ecological concern. Microplastics are plastic wastes with particulates less than 5 mm in size that are absorbed by sediments, water, atmosphere, and living organisms therefore affecting environmental and human health. This review focuses on the sources, transport, fate and factors influencing the release of microplastics into aquatic ecosystems and also highlights the possible impact of these toxic micro-sized particles on aquatic lives and human health. It also discusses the available microplastic challenges, remediation and perspective for microplastic pollution management as well as green strategies for reducing microplastic contamination in water bodies. Potential ecological and health risks emanate from their ability to adsorb and transport toxic chemicals, and ease of absorption into the cells of living organisms and interfering with physiological processes. Mitigation strategies have been identified to overcome effects of the microplastics on the environment including educational campaigns aimed at improving public awareness of the plastics contamination, encouraging reuse and recycling, placing prohibitions on microplastics-free (Microbead-Free) in personal care products, putting heavy fines for plastic consumers among others. Several methods for removing microplastics, are grouped into three categories: engineered, biodegradable, and bioengineered approaches. This review promotes concise literature on microplastics and encourages further studies among researchers on this aspect of science.